Vernalization and Floral Transition in Autumn Drive Winter Annual Life History in Oilseed Rape - O’Neill, Carmel M. (Curr Biol, 2019)
Plants with winter annual life history germinate in summer or autumn and require a period of prolonged winter cold to initiate flowering, known as vernalization. In the Brassicaceae, the requirement for vernalization is conferred by high expression of orthologs of the FLOWERING LOCUS C (FLC) gene, the expression of which is known to be silenced by prolonged exposure to winter-like temperatures [1]. Based on a wealth of vernalization experiments, typically carried out in the range of 5°C–10°C, we would expect field environments during winter to induce flowering in crops with winter annual life history. Here, we show that, in the case of winter oilseed rape, expression of multiple FLC orthologs declines not during winter but predominantly during October when the average air temperature is 10°C–15°C. We further demonstrate that plants proceed through the floral transition in early November and overwinter as inflorescence meristems, which complete floral development in spring. To validate the importance of pre-winter temperatures in flowering time control, we artificially simulated climate warming in field trial plots in October. We found that increasing the temperature by 5°C in October results in raised FLC expression and delays the floral transition by 3 weeks but only has a mild effect on flowering date the following spring. Our work shows that winter annuals overwinter as a floral bud in a manner that resembles perennials and highlights the importance of studying signaling events in the field for understanding how plants transition to flowering under real environmental conditions.